1998
DOI: 10.1046/j.1365-2648.1998.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing organizational practice and its relationship with other features of ward organization and job satisfaction

Abstract: This paper describes a new classification of ward organizational practice in nursing. Data related to aspects of ward nursing practice were collected by postal survey from a nationally representative sample of 74 acute hospital wards, and subjected to hierarchical cluster analysis. The model which was deemed to best 'fit' the data, provided three types of ward practices, which have been named: 'devolved', 'two tier' and 'centralized' nursing. The distinguishing features of the three classifications are similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 25 publications
0
79
2
2
Order By: Relevance
“…The analytic approach to taxonomy development is well established in the organizational literature [36] and has been applied to healthcare in a number of prior studies [37-39]. In this study, the unit of analysis was the care unit.…”
Section: Methodsmentioning
confidence: 99%
“…The analytic approach to taxonomy development is well established in the organizational literature [36] and has been applied to healthcare in a number of prior studies [37-39]. In this study, the unit of analysis was the care unit.…”
Section: Methodsmentioning
confidence: 99%
“…In the nursing field, hospitals use four models of organising nurses' work that range from a nurse doing all the nursing care for a patient, to care done by shifts or teams of nurses, to dividing outpatient care by tasks assigned to different nurses (Adams, Bond, and Hale 1998;Tiedeman and Lookinland 2004). In functional nursing, motivated by the argument of efficiency, the overall care for an individual patient is divided into disparate tasks; nurses are assigned these and then carry out the same task for all patients in a ward.…”
Section: The Organisation Of Educators' Workmentioning
confidence: 99%
“…As a result, many different staff members provide care for any one patient for the duration of their stay. This arrangement has been criticised for creating 'professional distance' between nurses and patients, for being mechanistic, and resembling an industrial production line (Adams, Bond, and Hale 1998). Likewise, to what extent is there 'professional distance' between the educator and the learner when educational work in museums is divided?…”
Section: The Organisation Of Educators' Workmentioning
confidence: 99%
“…Studies indicate that the frequency and duration of (direct) nursing care activities are closely correlated [10,14] and influenced by such factors as the methods of care provision [32], caregiver characteristics [33,34], patient characteristics [11][12][13] and the organizational structure [35]. A study by Lundgren and Segesten [9] with respect to a medical-surgical ward, for instance, showed that changing the staffing pattern through the introduction of a patient focused system of nursing delivery increased the time used for direct care.…”
Section: Theory On Direct Carementioning
confidence: 99%